Analysis Of Online Game Addiction With Sleep Quality Teenagers In Gorontalo - ika wulansari (Jambura Nursing Journal, 2023)
One of the problems in adolescents causes health problems such as feelings of tiredness, anxiety, lethargy, apathy, blackness around the eyes swollen eyelids, red conjunctiva, sore eyes, fragmented attention, headaches, and frequent yawning or drowsiness because teenagers often experience sleep disturbance that interrupt quality of their sleep. One of the things that causes this incident is playing online games. This research aims to determine the relationship between online game addiction and adolescents’ sleep quality at a senior high school in Gorontalo. This research employs a cross-sectional method. Data are obtained from 65 samples, 39 respondents (60%) in the addiction of game online category and 39 respondents (60%) in the category of poor sleep quality. The results indicate a relationship between online game addiction and adolescent sleep quality with a p-value of 0.000